Diagnostic and Therapeutic updates of Autoimmune Encephalitis: a Narrative Review (Sir Salimullah Medical College Journal, 2025)
Autoimmune encephalitis (AE) is a diverse collection of immune-mediated neurological illnesses that cause inflammation of the brain parenchyma by autoantibody-mediated pathways. AE encompasses a group of non-infectious immune-mediated inflammatory disorders of the brain parenchyma often involving the cortical or deep gray matter with or without involvement of the white matter, meninges, or the spinal cord. Suggested mechanisms that may trigger AE include tumors (paraneoplastic), infections (para-infectious), or it may be cryptogenic. This review summarises current knowledge about the pathogenesis, clinical presentation, diagnostic techniques, and treatment methods linked with AE. he wide range of autoantibodies targeting neuronal surface antigens, such as NMDA receptor, LGI1, and CASPR2 antibodies, is highlighted, as is their relationship to specific clinical characteristics. The paper discusses diagnostic techniques that include cerebrospinal fluid (CSF) analysis, magnetic resonance imaging (MRI), and autoantibody detection, as well as new biomarkers. The review emphasises developments in immunotherapy, such as corticosteroids, plasma exchange, intravenous immunoglobulin, and targeted monoclonal antibodies, and their impact on prognosis.Early diagnosis,differential diagnosis, and long-term management challenges are discussed, as well as future research opportunities for unravelling pathogenic pathways and optimising personalised treatment approaches. Understanding the complicated immunopathology of AE is critical for earlier diagnosis and treatment, which ultimately improves neurological outcomes.Sir Salimullah Med Coll J 2024; 32: 3-9